Dictionary of agricultural and environmental science - Troeh, Frederick R. (Iowa State Press, 2003)
This text provides an accurate and comprehensive dictionary of terms used in the agricultural and environmental sciences, it includes many biological, chemical, and health terms that are important for a full understanding of the subject fields. Presenting thousands of entries, many not found in similar dictionaries, this new reference contains the latest, most up to date definitions and designations of usage in the fields of agriculture, soil science, animal science, agricultural engineering and many more